Uploaded by chihin yim

Mathematics Formulae for F5 Students

advertisement
Mathematics Formulae for F5 Students
Trigonometry formulae
Basic trigonometry formulae
General solution
𝑠𝑖𝑛2 𝐴 + π‘π‘œπ‘  2 𝐴 = 1
𝑠𝑖𝑛 𝐴 → 180𝑛° + (−1)𝑛 𝐴
or π‘›πœ‹ + (−1)𝑛 𝐴
π‘‘π‘Žπ‘›2 𝐴 + 1 = 𝑠𝑒𝑐 2 𝐴
π‘π‘œπ‘  𝐴 → 360𝑛° ± 𝐴
or 2π‘›πœ‹ ± 𝐴
π‘π‘œπ‘‘ 2 𝐴 + 1 = 𝑐𝑠𝑐 2 𝐴
π‘‘π‘Žπ‘› 𝐴 → 180𝑛° + 𝐴
or π‘›πœ‹ + 𝐴
Half angle formulae
Double angle formulae
𝑠𝑖𝑛2
πœƒ 1
= (1 − π‘π‘œπ‘  πœƒ)
2 2
πœƒ 1
π‘π‘œπ‘ 
= (1 + π‘π‘œπ‘  πœƒ)
2 2
𝑠𝑖𝑛 2𝐴 = 2 𝑠𝑖𝑛 𝐴 π‘π‘œπ‘  𝐴
π‘π‘œπ‘  2𝐴 = π‘π‘œπ‘  2 𝐴 − 𝑠𝑖𝑛2 𝐴
2
π‘‘π‘Žπ‘›
πœƒ 1 − π‘π‘œπ‘  πœƒ
=
2
𝑠𝑖𝑛 πœƒ
= 2π‘π‘œπ‘  2 𝐴 − 1
= 1 − 2𝑠𝑖𝑛2 𝐴
π‘‘π‘Žπ‘› 2𝐴 =
2 π‘‘π‘Žπ‘› 𝐴
1 − π‘‘π‘Žπ‘›2 𝐴
Triple angle formulae
Compound Angle
𝑠𝑖𝑛 3𝐴 = 3 𝑠𝑖𝑛 𝐴 − 4𝑠𝑖𝑛3 𝐴
𝑠𝑖𝑛(𝐴 + 𝐡) = 𝑠𝑖𝑛 𝐴 π‘π‘œπ‘  𝐡 + π‘π‘œπ‘  𝐴 𝑠𝑖𝑛 𝐡
π‘π‘œπ‘  3𝐴 = 4 π‘π‘œπ‘  3 𝐴 − 3 π‘π‘œπ‘  𝐴
𝑠𝑖𝑛(𝐴 − 𝐡) = 𝑠𝑖𝑛 𝐴 π‘π‘œπ‘  𝐡 − π‘π‘œπ‘  𝐴 𝑠𝑖𝑛 𝐡
3 π‘‘π‘Žπ‘› 𝐴 − π‘‘π‘Žπ‘›3 𝐴
π‘‘π‘Žπ‘› 3𝐴 =
1 − 3π‘‘π‘Žπ‘›2 𝐴
π‘π‘œπ‘ (𝐴 + 𝐡) = π‘π‘œπ‘  𝐴 π‘π‘œπ‘  𝐡 − 𝑠𝑖𝑛 𝐴 𝑠𝑖𝑛 𝐡
Sine and Cosine formulae
π‘Ž
𝑏
𝑐
=
=
𝑠𝑖𝑛 𝐴 𝑠𝑖𝑛 𝐡 𝑠𝑖𝑛 𝐢
π‘Ž2 = 𝑏 2 + 𝑐 2 − 2𝑏𝑐 π‘π‘œπ‘  𝐴
π‘π‘œπ‘ (𝐴 − 𝐡) = π‘π‘œπ‘  𝐴 π‘π‘œπ‘  𝐡 + 𝑠𝑖𝑛 𝐴 𝑠𝑖𝑛 𝐡
π‘‘π‘Žπ‘›(𝐴 + 𝐡) =
π‘‘π‘Žπ‘› 𝐴 + π‘‘π‘Žπ‘› 𝐡
1 − π‘‘π‘Žπ‘› 𝐴 π‘‘π‘Žπ‘› 𝐡
π‘‘π‘Žπ‘›(𝐴 − 𝐡) =
π‘‘π‘Žπ‘› 𝐴 − π‘‘π‘Žπ‘› 𝐡
1 + π‘‘π‘Žπ‘› 𝐴 π‘‘π‘Žπ‘› 𝐡
Product to sum formulae
Sum to product formulae
1
𝑠𝑖𝑛 𝐴 π‘π‘œπ‘  𝐡 = [𝑠𝑖𝑛(𝐴 + 𝐡) + 𝑠𝑖𝑛(𝐴 − 𝐡)]
2
𝑠𝑖𝑛 𝐴 + 𝑠𝑖𝑛 𝐡 = 2 (𝑠𝑖𝑛
𝐴+𝐡
𝐴−𝐡
π‘π‘œπ‘ 
)
2
2
1
π‘π‘œπ‘  𝐴 𝑠𝑖𝑛 𝐡 = [𝑠𝑖𝑛(𝐴 + 𝐡) − 𝑠𝑖𝑛(𝐴 − 𝐡)]
2
𝑠𝑖𝑛 𝐴 − 𝑠𝑖𝑛 𝐡 = 2 (π‘π‘œπ‘ 
𝐴+𝐡
𝐴−𝐡
𝑠𝑖𝑛
)
2
2
π‘π‘œπ‘  𝐴 π‘π‘œπ‘  𝐡 =
1
[π‘π‘œπ‘ (𝐴 + 𝐡) + π‘π‘œπ‘ (𝐴 − 𝐡)]
2
1
𝑠𝑖𝑛 𝐴 𝑠𝑖𝑛 𝐡 = − [π‘π‘œπ‘ (𝐴 + 𝐡) − π‘π‘œπ‘ (𝐴 − 𝐡)]
2
π‘π‘œπ‘  𝐴 + π‘π‘œπ‘  𝐡 = 2 (π‘π‘œπ‘ 
𝐴+𝐡
𝐴−𝐡
π‘π‘œπ‘ 
)
2
2
π‘π‘œπ‘  𝐴 − π‘π‘œπ‘  𝐡 = −2 (𝑠𝑖𝑛
𝐴+𝐡
𝐴−𝐡
𝑠𝑖𝑛
)
2
2
Differentiation and Integration formulae
Limit
π‘™π‘–π‘š
1
=0
π‘₯→∞ π‘₯
𝑒π‘₯ − 1
π‘™π‘–π‘š
=1
π‘₯→0
π‘₯
1
=0
π‘₯→−∞ π‘₯
1 π‘₯
π‘™π‘–π‘š (1 + ) = 𝑒
π‘₯→∞
π‘₯
1 π‘₯
π‘™π‘–π‘š (1 + ) = 1
π‘₯→0
π‘₯
π‘™π‘–π‘š(1 + π‘₯)π‘₯ = 𝑒
π‘™π‘–π‘š
π‘™π‘–π‘š
π‘₯→0
𝑠𝑖𝑛 π‘₯
π‘₯
= 1 ; π‘™π‘–π‘š
1
π‘₯→0
π‘‘π‘Žπ‘› π‘₯
π‘₯→0
π‘₯
=1
π‘Ž π‘₯
π‘™π‘–π‘š (1 + ) = 𝑒 π‘Ž
π‘₯→∞
π‘₯
π‘™π‘–π‘š π‘Ž π‘₯ = 0 where 0 < π‘Ž < 1
π‘₯→∞
π‘™π‘–π‘š π‘Ž π‘₯ = ∞ where 0 < π‘Ž < 1
π‘₯→−∞
π‘™π‘–π‘š π‘Ž π‘₯ = ∞ where π‘Ž > 1
π‘₯→∞
π‘™π‘–π‘š π‘Ž π‘₯ = 0 where π‘Ž > 1
π‘₯→−∞
Differentiation formula
𝑑 𝑛
π‘₯ = 𝑛π‘₯ 𝑛−1
𝑑π‘₯
𝑑 π‘₯
π‘Ž = π‘Ž π‘₯ 𝑙𝑛 π‘Ž
𝑑π‘₯
𝑑
𝑑𝑣
𝑑𝑒
𝑒𝑣 = 𝑒
+ 𝑣
𝑑π‘₯
𝑑π‘₯
𝑑π‘₯
𝑑
𝑑𝑒 𝑑𝑣
(𝑒 + 𝑣) =
+
𝑑π‘₯
𝑑π‘₯ 𝑑π‘₯
𝑑 π‘₯
𝑒 = 𝑒π‘₯
𝑑π‘₯
𝑑𝑒
𝑑𝑣
𝑣
−𝑒
𝑑 𝑒
( ) = 𝑑π‘₯ 2 𝑑π‘₯
𝑑π‘₯ 𝑣
𝑣
𝑑
𝑑𝑒 𝑑𝑣
(𝑒 − 𝑣) =
−
𝑑π‘₯
𝑑π‘₯ 𝑑π‘₯
𝑑
1
𝑙𝑛 π‘₯ =
𝑑π‘₯
π‘₯
𝑑
𝑑π‘₯
(π‘₯ 𝑝 − π‘₯ + 𝑐)𝑛 = 𝑛(π‘₯ 𝑝 − π‘₯ + 𝑐)𝑛−1 (𝑝π‘₯ 𝑝−1 − 1) where p and n are any integers
Integration formulae
∫ π‘₯ 𝑛 𝑑π‘₯ =
π‘₯ 𝑛+1
+𝐢
𝑛+1
∫
1
𝑑π‘₯ = 𝑙𝑛 π‘₯ + 𝐢
π‘₯
π‘Žπ‘₯
+𝐢
𝑙𝑛 π‘Ž
∫ 𝑒 π‘₯ 𝑑π‘₯ = 𝑒 π‘₯ + 𝐢
∫ 𝑒 𝑑𝑣 = 𝑒𝑣 − ∫ 𝑣 𝑑𝑒
∫ π‘Ž π‘₯ 𝑑π‘₯ =
Trigonometry differentiation formula
Trigonometry integration formulae
𝑑
𝑠𝑖𝑛 π‘₯ = π‘π‘œπ‘  π‘₯
𝑑π‘₯
∫ π‘π‘œπ‘  π‘₯ 𝑑π‘₯ = 𝑠𝑖𝑛 π‘₯ + 𝐢
∫ 𝑠𝑒𝑐 π‘₯ 𝑑π‘₯ = 𝑙𝑛|𝑠𝑒𝑐 𝑒 + π‘‘π‘Žπ‘› 𝑒| + 𝐢
𝑑
π‘π‘œπ‘  π‘₯ = − 𝑠𝑖𝑛 π‘₯
𝑑π‘₯
∫ 𝑠𝑖𝑛 π‘₯ 𝑑π‘₯ = − π‘π‘œπ‘  π‘₯ + 𝐢
∫ 𝑐𝑠𝑐 π‘₯ 𝑑π‘₯ = −𝑙𝑛|𝑐𝑠𝑐 π‘₯ + π‘π‘œπ‘‘ π‘₯| + 𝐢
𝑑
π‘‘π‘Žπ‘› π‘₯ = 𝑠𝑒𝑐 2 π‘₯
𝑑π‘₯
∫ 𝑠𝑒𝑐 2 π‘₯ 𝑑π‘₯ = π‘‘π‘Žπ‘› π‘₯ + 𝐢
∫ π‘‘π‘Žπ‘› π‘₯ 𝑑π‘₯ = 𝑙𝑛|𝑠𝑒𝑐 π‘₯| + 𝐢
𝑑
π‘π‘œπ‘‘ π‘₯ = − 𝑐𝑠𝑐 2 π‘₯
𝑑π‘₯
∫ 𝑐𝑠𝑐 2 π‘₯ 𝑑π‘₯ = −π‘π‘œπ‘‘π‘₯ + 𝐢
∫ π‘π‘œπ‘‘ π‘₯ 𝑑π‘₯ = 𝑙𝑛|𝑠𝑖𝑛 π‘₯| + 𝐢
𝑑
𝑠𝑒𝑐 π‘₯ = π‘‘π‘Žπ‘› π‘₯ 𝑠𝑒𝑐 π‘₯
𝑑π‘₯
∫ 𝑠𝑒𝑐 π‘₯ π‘‘π‘Žπ‘› π‘₯ 𝑑π‘₯ = 𝑠𝑒𝑐 π‘₯ + 𝐢
∫
𝑑
𝑐𝑠𝑐 π‘₯ = − π‘π‘œπ‘‘ π‘₯ 𝑐𝑠𝑐 π‘₯
𝑑π‘₯
∫ π‘π‘œπ‘‘ π‘₯ 𝑐𝑠𝑐 π‘₯ 𝑑π‘₯ = − 𝑐𝑠𝑐 π‘₯ + 𝐢
∫
∫ 𝑙𝑛 π‘₯ 𝑑π‘₯ = π‘₯ 𝑙𝑛 π‘₯ − π‘₯ + 𝐢
∫
𝑑π‘₯
√π‘Ž2
−
π‘₯2
π‘₯
= 𝑠𝑖𝑛 −1 ( ) + 𝐢
π‘Ž
𝑑π‘₯
π‘₯
= π‘‘π‘Žπ‘›−1 ( ) + 𝐢
π‘Ž2 + π‘₯ 2
π‘Ž
𝑑π‘₯
π‘₯√π‘₯ 2
−
π‘Ž2
π‘₯
= 𝑠𝑒𝑐 −1 | | + 𝐢
π‘Ž
Download